2016
DOI: 10.1073/pnas.1518244113
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-AB and 5-Azacytidine induce conversion of somatic cells into tissue-regenerative multipotent stem cells

Abstract: Current approaches in tissue engineering are geared toward generating tissue-specific stem cells. Given the complexity and heterogeneity of tissues, this approach has its limitations. An alternate approach is to induce terminally differentiated cells to dedifferentiate into multipotent proliferative cells with the capacity to regenerate all components of a damaged tissue, a phenomenon used by salamanders to regenerate limbs. 5-Azacytidine (AZA) is a nucleoside analog that is used to treat preleukemic and leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 47 publications
5
46
0
Order By: Relevance
“…Furthermore, recent works carried out in other laboratories demonstrated the possibility to convert human skin fibroblasts into neural progenitor-like cells (Mirakhori et al, 2015) and mature bone and fat cells into tissue-regenerative multipotent stem (iMS) cells (Chandrakanthan et al, 2016) through the use of the demethylating agent 5-aza-CR, proving to be in agreement with our results. In addition, Cheng et al reported that, using a cocktail containing inhibitors of histone deacetylation, glycogen synthase kinase and TGF-β pathway, it is possible to convert human and murine fibroblasts into proliferating chemical-induced neural progenitor cells (ciNPC), under physiological hypoxic conditions (5% O2; Cheng et al, 2015).…”
Section: Epigenetic Conversion: An Alternative Erasing Of "Epigeneticsupporting
confidence: 92%
“…Furthermore, recent works carried out in other laboratories demonstrated the possibility to convert human skin fibroblasts into neural progenitor-like cells (Mirakhori et al, 2015) and mature bone and fat cells into tissue-regenerative multipotent stem (iMS) cells (Chandrakanthan et al, 2016) through the use of the demethylating agent 5-aza-CR, proving to be in agreement with our results. In addition, Cheng et al reported that, using a cocktail containing inhibitors of histone deacetylation, glycogen synthase kinase and TGF-β pathway, it is possible to convert human and murine fibroblasts into proliferating chemical-induced neural progenitor cells (ciNPC), under physiological hypoxic conditions (5% O2; Cheng et al, 2015).…”
Section: Epigenetic Conversion: An Alternative Erasing Of "Epigeneticsupporting
confidence: 92%
“…They confirmed that specific chemical compounds can push cells to a transient less committed state, increasing cell plasticity for a relative short time-window, but sufficient to re-address an adult mature cell into another differentiated cell type (Harris et al, 2011;Pennarossa et al, 2013Pennarossa et al, , 2014Brevini et al, 2014;Mirakhori et al, 2015;Chandrakanthan et al, 2016).…”
Section: Epigenetic Conversion: An Alternative Erasing Of "Epigeneticmentioning
confidence: 94%
“…More recent experiments demonstrated that a brief exposure to a demethylating agent can push cells to a less committed state, increasing their plasticity for a short window of time sufficient to re-address cells towards a different cell type [27]. The starting hypothesis was that the processes associated with differentiation are driven by several mechanisms.…”
Section: Reviewmentioning
confidence: 99%
“…Among these, DNA methylation plays a fundamental role during both early embryonic development and cell lineage specification, causing silencing of large fraction of the genome and subsequent expression of gene essential for the maintenance of the differentiated and tissue-specific phenotype. Based on this, 5-azacytidine (5-aza-CR), a well-characterized DNMT inhibitor, was selected in order to remove the epigenetic “blocks” that are responsible for tissue specification [35, 7]. This drug is a chemical analog of cytosine, it can be incorporated into DNA and RNA, causing an increased effect in resting as well as in dividing cells, and it is known to be a direct inhibitor of methylation in newly synthesized DNA by blocking DNMT function [56].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation